Assessment of the level of formation of values of healthy lifestyle of students - Імас, Євгеній; Дутчак, Мирослав; Андрєєва, Олена; Кенсицька, Ірина (Slobozhanskyi Herald of Science and Sport, 2019)
Yevheniy Imas, Myroslav Dutchak, Olena Andrieieva & Iryna Kensytska Purpose: theoretically substantiate, develop and experimentally test a system for assessing the level of formation of the values of a healthy lifestyle of students in the process of physical education. Material & Methods: to achieve this goal, such research methods were used – analysis and synthesis of literature sources and documentary materials, pedagogical observation, pedagogical testing, pedagogical experiment, sociological research methods (questioning), anthropometry method, methods for determining the functional state of the body, methods for assessing the level of physical health ((according to G. L. Apanasenko method), methods for determining motor activity, testing theoretical knowledge, methods of mathematical statistics. The study involved 108 students and 120 female students of higher educational institutions in Kiev. Results: the components of the students' value attitude to a healthy lifestyle are defined and the criteria and indicators of their formation are refined: cognitive (knowledge about health, healthy lifestyle, health values, axiological attitudes to achieve the goal), motivational and value (attitude to one’s own health, positive emotions, interest and needs for a healthy lifestyle), activity (actions and behavior, contribute to a healthy lifestyle, compliance with the requirements of a healthy lifestyle in everyday life). On the basis of certain criteria and indicators, the levels of formation of the values of a healthy lifestyle are characterized: high, sufficient, satisfactory and critical. It was revealed that the majority of students have a critical level of formation of values of a healthy lifestyle (boys – 75,93%, girls – 72,5%). Conclusion: the existing developments in assessing the attitude of students towards a healthy lifestyle and the development of their attitude towards recreational activities have been further developed; based on the analysis of empirical research data, a significant discrepancy was noted between the declared value of health, a healthy lifestyle, and behavioral attitudes of students. On the basis of the obtained data, we proposed the directions of modernization of physical education of students, to promote the formation of values of a healthy lifestyle.